Comparison of Modelling Strategies of R.C Walls for Seismic Analysis. Issue 1 (November 2021) - Jeelani, Syed Hamim; Akhtar, Salim; Lingeshwaran, N; Jagarapu, Durga Chaitanya Kumar; Mohammed Aslam, M A; Nallusamy, Babu; Rizvi, Syed Shams
Abstract: Reinforced concrete walls are being widely adopted as lateral load resisting systems for high rise structures. The current practice among design engineers for modelling of such walls is by idealizing the same as 'wide' columns, which is uncertain from safety as well as economy point of view. The most efficient modelling strategy of RC walls involves use of shell elements. Such an approach can be computationally much intensive, especially from a seismic analysis perspective. The present study utilizes an equivalent strut approach for modelling RC walls. The modelling strategy is demonstrated on a G + 15 storey residential apartment located in Calicut city. The proposed methodology will be compared with the traditional 'wide' column method as well as the one with shell element discretization. Comparison of modal properties such as frequencies and vibration modes from the various models are initially made to assess the model accuracy. Various seismic analyses viz. Equivalent static approach, Response spectrum approach and the assessment the storey shear, inter storey drifts as well as computation times using various models were performed using time history analysis. From preliminary results, it is understood that the modelling strategy could serve as an efficient alternative to more robust and computationally demanding scheme involving use of shell elements.